Epistemologi Keilmuan Integratif-Interkonektif M. Amin Abdullah dan Resolusi Konflik - Dendi Sutarto (Program Studi Ilmu Pemerintahan Fakultas Ilmu Sosial dan ilmu Politik Universitas Riau Kep, 2017)
Abstract The interconnectivity paradigm, axiologically, wants to offer a new, more open, dialogue and dialogue view of the world of human beings and scientists, able to open dialogue and cooperation, be transparent, accountable to the public and forward-looking. While ontologically, the relationship between the various disciplines of science becomes more open and dialogue of scholarship derived from the texts (Hadlarah al-Nash), and the factual-historical-empirical scholarly culture, social sciences and the natural sciences (Hadlarah al-Ilm ) as well as ethical-philosophical science culture (Hadlarah al-Falsafah). This paper argues that the thought of M. Amin Abdullah contributed greatly to scholarship related to contemporary humanisties approaches, such as hermeneutics, contemporary linguistics, the natural sciences, by revealing the scientific treasures of Bayani, Burhani and Irfani in the Islamic cultural tradition. Both traditions are attempted to compare in matrices and then deliver on a choice of scientific formats that are integrative and interconnective and able to disperse the tensions of religious social conflict in multicultural societies. Keywords: M. Amin Abdullah, integrative-interconetive science, conflict resolution, epistimologi Abstrak Paradigma interkoneksitas, secara aksiologi, ingin menawarkan pandangan dunia (word view) manusia beragama dan ilmuan yang baru, yang lebih terbuka, mampu membuka dialog dan kerjasama, transparan, dapat dipertanggungjawabkan secara publik dan berpandangan ke depan. Sedangkan secara ontologis, hubungan antara berbagai disiplin keilmuan menjadi semakin terbuka dan mendialogkan keilmuan bersumber pada teks-teks (Hadlarah al-Nash), dan budaya keilmuan faktual-historis-empiris yakni ilmu-ilmu sosial dan ilmu-ilmu kealaman (Hadlarah al-Ilm) serta budaya keilmuan etis-fiosofis (Hadlarah al-Falsafah). Tulisan ini berpendapat bahwa pemikiran M. Amin Abdullah berkontribusi besar bagi keilmuan terkait pendekatan humanisties-kontemporer, seperti hermeneutik, linguistis kontemporer, ilmu-ilmu kealaman, dengan mengungkap kembali kekuatan khazanah keilmuan Bayani, Burhani dan Irfani dalam tradisi budaya Islam. Kedua tradisi tersebut dicoba dibandingkan dalam matrik dan kemudian mengantarkan pada suatu pilihan format keilmuan yang bersifat integratif dan interkonektif dan mampu meredahkan ketegangan konflik sosial keagamaan dalam masyarakat multikulturalisme. Keywords: M. Amin Abdullah, integratif-interkonetif keilmuan, resolusi konflik,epistimologi